Design of an automated system for the classification of plastic and glass bottles using sound (2022)
Nowadays, The Internet of Things (IoT) is a valuable tool which allows companies to automate and control their processes in a more efficient way by interconnecting hardware and software. For this project, we designed an automated system intended to classify elements in a recycling process. This was done by applying Deep Learning and audio processing techniques, as well as by interconnecting a conveyor band, a robot arm, and an audio frequency sensor via various IoT communication protocols. The result is a fully automated system, which successfully classifies bottles based on the sound made when hit, with an accuracy of over 90%